(untitled) (Journal of Contemporary Philology, 2025)
The significant influx of Anglicisms into the Macedonian language has become an undeniable linguistic phenomenon. Anglicisms appear in various domains such as information technology, law, business, social welfare and science. They reflect the influence of English over Macedonian as well as the interest of the Macedonian society. The analysis is qualitative and it is based on a randomly collected corpus of 300 Anglicisms that appear in the Macedonian language from the beginning of the 21st century. The research, first, focuses on the identification and classification of visible Anglicisms and criteria that verify their visibility, and then it contrasts them with the loan translations. The study also examines the patterns of borrowing Anglicisms into Macedonian, focusing on the distinction between direct lexical borrowings and calques or loan translations. It aims to determine why certain English expressions are directly incorporated into the Macedonian language, while others are translated part by part, sometimes coexisting with their original English forms. Certain tendencies are noted, based on the analysis, which indicate that socio-cultural factors play more significant role than linguistic circumstances when establishing the predictable patterns of borrowing.